Atbildība par nolēmuma par aizsardzību pret vardarbību nepildīšanu - Allika, Agnese (Latvijas Universitāte, 2023)
Bakalaura darba tēma ir “Atbildība par nolēmuma par aizsardzību pret vardarbību nepildīšanu”. Darba mērķis ir noskaidrot nolēmuma par aizsardzību pret vardarbību nepildīšanas sekas, salīdzināt situāciju Latvijā un citās valstīs, rast risinājumu, ieteikumus, lai veicinātu nolēmuma pildīšanu. Tika aplūkoti dažādu valstu normatīvie akti vardarbības ģimenē apkarošanas jomā. Darba uzdevumi ir izpētīt tiesību avotus par vardarbību ģimenē un tās apkarošanu, darba gaitā atrast regulējuma trūkumus, saistībā ar nolēmuma par pagaidu aizsardzību pret vardarbību nepildīšanu, izdarīt secinājumus par pagaidu aizsardzības pret vardarbību nepildīšanas regulējumu Latvijā un citās valstīs, piedāvāt risinājumus, ieteikumus regulējuma trūkumu novēršanai. Darbā tiek analizēts Krimināllikuma 168.1 pantā noteiktā noziedzīgā nodarījuma sastāvs, izpētīti norobežošanas gadījumi. Autore darbā secinājusi, ka normatīvajos aktos veicami grozījumi, lai aizsardzību pret vardarbību padarītu efektīvāku, iesaistot arī citas institūcijas, kā piemēram, sociālos dienestus un policiju.

The topic of the Bachelor is "Responsibility for non-compliance with the decision on protection against violence". The aim of the work is to find out the consequences of non-implementation of the decision on protection against violence, compare the situation in Latvia and other countries, find a solution, recommendations to promote the implementation of the decision. The author was examined the normative acts of different countries in the field of combating domestic violence. The tasks of the work are to study the sources of law on domestic violence and combating it, in the course of the work to find deficiencies in the regulation, in connection with the decision on non-implementation of temporary protection against violence, to draw conclusions about the regulation of temporary protection against violence in Latvia and other countries, to offer solutions, recommendations for the elimination of regulatory deficiencies. The work analyzes the composition of the criminal offense defined in Article 168.1 of the Criminal Law, investigates cases of confinement. The author has concluded in her work that amendments should be made to the regulatory acts to make protection against violence more effective, involving other institutions, such as social services and the police.
Resposibility for non-compliance with the decision on protection against violence
Keywords: Juridiskā zinātne; pagaidu aizsardzība pret vardarbību; vardarbība; norobežošana; Civilprocesa likums; Krimināllikums